Graduación 2017 40 aniversario. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2017)
Cynthia Fallas Hernández,Tatiana Bermúdez Vargas,Violeta Díaz Fernández y Erick Corrales Arroyo
Colección Fototeca UNED
Keywords: Fallas Hernández, Cynthia; Bermúdez Vargas, Tatiana; Díaz Fernández, Violeta; Corrales Arroyo, Erick; FOTOGRAFÍA; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA